Synthesis and PI3 Kinase Inhibition Activity of a Wortmannin-Leucine Derivative - Cantrell, William (Molecules, 2018)
Wortmannin is a potent covalent inhibitor of PI3K that shows substantial in vivo toxicity and thus is unsuitable for systemic therapeutic applications. One possible approach to minimize systemic toxicity is to generate a latent wortmannin pro-drug that will be selectively activated in target tissues. To test this approach, a wortmannin derivative with a leucine linker attached to C20 has been synthesized and tested for inhibition of PI3K activity in prostate cancer cells. Analysis of PI3K pathway inhibition by Wormannin-Leu (Wn-L) and intact Wortmannin (Wn) showed that attachment of Leu at C-20 decreased potency of PI3K pathway inhibition 10-fold compared to intact wortmannin, yet exceeded the potency of a competitive PI3K inhibitor LY294002.